Network function virtualization : concepts and applicability in 5G networks - Zhang, Ying, 1982- (John Wiley & Sons, Inc., 2018)
A horizontal view of newly emerged technologies in the field of network function virtualization (NFV), introducing the open source implementation efforts that bring NFV from design to reality -- This book explores the newly emerged technique of network function virtualization (NFV) through use cases, architecture, and challenges, as well as standardization and open source implementations. It is the first systematic source of information about cloud technologies' usage in the cellular network, covering the interplay of different technologies, the discussion of different design choices, and its impact on our future cellular network. -- Network Function Virtualization: Concepts and Applicability in 5G Networks reviews new technologies that enable NFV, such as Software Defined Networks (SDN), network virtualization, and cloud computing. It also provides an in-depth investigation of the most advanced open source initiatives in this area, including OPNFV, Openstack, and Opendaylight. Finally, this book goes beyond literature review and industry survey by describing advanced research topics such as service chaining, VNF orchestrations, and network verification of NFV systems. In addition, this resource: . Introduces network function virtualization (NFV) from both industrial and academic perspectives. Describes NFV's usage in mobile core networks, which is the essence of 5G implementation. Offers readers a deep dive on NFV's enabling techniques such as SDN, virtualization, and cloud computing -- Network Function Virtualization: Concepts and Applicability in 5G Networks is an ideal book for researchers and university students who want to keep up with the ever-changing world of network function virtualization.